POTENSI ANTIDIABETES EKSTRAK ETANOL DAUN KOPASANDA (Chromolaena odorata L.) DENGAN METODE SPEKTROFOTOMETRI UV-Vis - Rahmawati, Rahmawati; Widiastuti, Harti; Puspita, Della (Fakultas Farmasi UMI, 2024)
Diabetes Mellitus (DM) is a chronic metabolic disease characterized by an increase in glucose levels in the blood. There are many treatment efforts to control and reduce blood glucose levels with natural ingredients. One of the treatment efforts that is expected to treat diabetes comes from plants, namely kopasanda leaves which have many benefits and contain several main compounds such as tannins, phenols, flavonoids, saponins and steroids. Secondary metabolite compounds such as phenols, flavonoid alkaloids and steroids have the potential to act as antidiabetics. The aim of this research was to determine the antidiabetic potential of ethanol extract of kopasanda leaves (Chromolaena odorata L.) in vitro using the Nelson-Somogyi reagent with the UV-Vis spectrophotometric method. The test was carried out by making a series of concentrations of ethanol extract of kopasanda leaves (Chromolaena odorata L.), namely 5, 10, 15, 20, 25 and 30 ppm using a UV-Vis spectrophotometer measured at a maximum wavelength of 749 nm. From the results of testing the antidiabetic potential of kopasanda leaves (Chromolaena odorata L.) in vitro, it was found that the equation y = 1.5986x + 38.183 with a correlation coefficient (r) = 0.9775 and an EC50 value of 7.3920 µg/mL showed that the leaf sample Kopasanda has potential as an antidiabetic